Active metal brazing and characterization of silicon nitride-to-metal joints - Baer, Casandra J (My University, 2010)
Active metal brazing of Inconel and titanium to turbine grade silicon nitride, widely acknowledged to be one of the most difficult ceramics to join to metals, was demonstrated for NASA?s Subsonic Rotary Wing project. A titaniumcontaining active braze, Cu-ABA (brazing temperature ~1297 K) was used in foil form together with judiciously arranged interlayers of Ni, W, Mo, Ta, Cu, and Kovar to manage residual stresses in joints. The joints were vacuum brazed and examined for microstructure, composition, and microhardness using optical microscopy, scanning electron microscopy, energy dispersive spectroscopy, and microhardness testing. Interlayers of Ta and W; Ni and W; Kovar and W; and Ni, W, Ni led to sound joints of Si3N4 with Inconel-625 and Ti; however, micro-cracking occurred within Si3N4 in some systems without loss of joint integrity. The formation of interfacial reaction layers enriched in Ti and Si (possibly a titanium silicide phase) suggested chemical reaction-induced bonding. Self-joined Si3N4 displayed the best joint characteristics
Keywords: Silicon nitrides--Brazing; Ceramic to metal bonding; Brazing